Brain activation and heart rate variability as markers of autonomic function under stress - Huber, Annika; Koenig, Julian; Bruns, Bastian; Bendszus, Martin; Friederich, Hans-Christoph; Simon, Joe J. (Scientific reports, 2025)
Efficient brain-heart interactions, mediated by the central autonomic network (CAN), are crucial in regulating physiological and psychological stress. The ability of the autonomic nervous system to adapt to stress predicts resilience to cardiovascular, anxiety, and mood disorders. Since the neural dynamics underlying brain-heart interactions remain poorly understood, this study investigated brain activation and heart rate variability (HRV) during stress and relaxation. Functional magnetic resonance imaging (fMRI) and peripheral heart rate assessment were used to assess brain-heart coupling during breathing-induced relaxation, psychosocial stress and stress recovery in 32 healthy participants. We assessed the relation between perceived stress and brain activation, and employed non-linear generalized additive models to forecast changes in HR based on brain activation in the CAN. Both breathing-induced relaxation and stress induction significantly affected HR variation and triggered brain activation in CAN-related regions. HR variation was related to CAN activity during stress induction, and that chronic stress was linked to reduced brain activation during stress recovery. Finally, we demonstrated that brain activation within the CAN predicts changes in HRV. Our results offer novel insights into dynamic brain-heart interactions during stress-related autonomic regulation and emphasize the brain-heart axis’s potential as a target for therapeutic interventions aimed at enhancing stress resilience.
Gesehen am 30.11.2025